PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE HOLLYWOOD SQUARES REVIEW TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS X SMAN 3 LENGAYANG KABUPATEN PESISIR SELATAN - Dewi, Yunita Sandra; Mirna, Mirna; Cesaria, Anna (Pendidikan Matematika, 2013)
This research is motivated by the lack of understanding of math concepts class X student of SMAN 3 Lengayang. One attempt to do is to apply the Hollywood Squares Strategy Review. This study aims to determine the students understanding of mathematical concepts by applying active learning strategies Hollywood Squares Review type is better than the students understanding of mathematical concepts with conventional learning in class X SMAN 3 Lengayang. This type of research is experimental research study design Against Random Subjects. Instrument in this study is the final test with indicator of understanding the concept. The data analysis technique used is the one party t test with the help of Minitab software. Hypothesis test results obtained P-value = 0.004 is less than Î± = 0.05, then the hypothesis in this study received. It can be concluded that the students understanding of mathematical concepts by applying Active Learning Strategies Hollywood Squares Review type is better than the students understanding of mathematical concepts with conventional learning in class X SMAN 3 Lengayang.Â